2003
DOI: 10.1152/ajprenal.00342.2002
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin II is a nitric oxide-dependent vasodilator and natriuretic peptide in the rat kidney

Abstract: Recent studies have indicated that urotensin II (UII), a cyclic peptide, is vasoactive and may be involved in cardiovascular dysfunctions. It remains unknown, however, whether UII plays a role in the control of renal vascular tone and tubular function. In the present study, a continuous infusion of synthetic human UII (hUII) into the renal artery (RA) in anesthetized rats was found to increase renal blood flow (RBF) and urinary water and sodium excretion (UV and UNaV) in a dose-dependent manner. At a dose of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 37 publications
7
77
2
1
Order By: Relevance
“…Other groups have reported a variety of renal responses to UTS infusion in the rat. Zhang et al (2003) observed an increase in fractional sodium excretion following intra-renal infusion of hUTS, but this was seen against a rather different background of diuresis and natriuresis accompanied by no change in GFR. By contrast, Ovcharenko et al (2006) observed no change in sodium excretion or fractional excretion of sodium in response to bolus injections of hUTS in Wistar rats.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Other groups have reported a variety of renal responses to UTS infusion in the rat. Zhang et al (2003) observed an increase in fractional sodium excretion following intra-renal infusion of hUTS, but this was seen against a rather different background of diuresis and natriuresis accompanied by no change in GFR. By contrast, Ovcharenko et al (2006) observed no change in sodium excretion or fractional excretion of sodium in response to bolus injections of hUTS in Wistar rats.…”
Section: Discussionmentioning
confidence: 90%
“…Previous clearance studies in rats have injected bolus doses systemically at 1-100 nmol/kg (Ovcharenko et al 2006) or infused at 2 . 5-20 ng/kg per min directly into the renal artery (Zhang et al 2003), which potentially exposed the kidney to supraphysiological doses of the hormone. The heterologous nature of the peptides used in these studies is unlikely to have had a significant impact on the outcome, as the UTSR is unable to distinguish between UTS from a number of species, including humans and rats (Labarrere et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of UII in the kidney is not clear at present. It has been shown to promote endothelial NO-mediated vasodilation in rat renal arteries accompanied by a dosedependent increase in renal blood flow and an increased urinary water and sodium excretion, but opposite effects have also been reported (Zhang et al 2003, Ashton 2006, Song et al 2006. It has been suggested that these discrepancies might result from the limited amounts of unoccupied receptors for binding exogenous UII (Qi et al 2005).…”
Section: Uts2r5mentioning
confidence: 99%
“…Continuous infusion of U-II into the renal artery of anesthetized rats caused nitric oxide-dependent increases in GFR, urinary water excretion, and urinary sodium excretion. 5 This effect may be possibly explained by reduced renal functions and fluid overload association. In a model of arteriovenous fistula induced high-output heart failure, incremental injection of U-II caused mean arterial pressure lowering, both in failing heart and in healthy controls.…”
Section: Introductionmentioning
confidence: 99%